Conjugate Electrospun 3D Gelatin Nanofiber Sponge for Rapid Hemostasis (Adv. Healthcare Mater. 20/2021). Issue 20 (21st October 2021) - Xie, Xianrui; Li, Dan; Chen, Yujie; Shen, Yihong; Yu, Fan; Wang, Wei; Yuan, Zhengchao; Morsi, Yosry; Wu, Jinglei; Mo, Xiumei
Abstract : Nanofiber Sponges In article number 2100918, Jinglei Wu, Xiumei Mo, and co‐workers develop a novel conjugate electrospinning strategy to prepare a 3D nanofiber sponge with low density, high surface area, compressibility. This method can be widely used in the preparation of various polymer nanofiber sponges. The obtained gelatin nanofiber sponge holds great potential as an absorbable hemostatic agent for rapid hemostasis.